Clay Tablets and Cones in the New Brunswick Museum, Saint John - George, Lynne С.
B1 44.311-326 and 328, all in photos. 311-313: clay cones Entemena, Gudea, Lipit-Ištar; 314-322: Wirtschaftsurkunden Ur III; 323-324: aB Wirtschaftsurkunden; 325: nB Urkunde, Nebukadnezar II.; 326: aB Rollsiegel; 328: Wirtschaftsurkunde Ur III, AS4